Efectividad de los programas de entrenamiento preventivo en lesiones del ligamento cruzado anterior. - Santillán Oleas, Mariela Fernanda (2026)
Introduction. Anterior cruciate ligament injuries (ACL) represent a major problem in the athlete population, with high incidence rates and negative physical, psychological, and economic consequences, including an increased risk of early osteoarthritis and difficulties in returning to sport. Most of these lesions are non-contact and related to preventable neuromuscular and biomechanical deficits. Objective. Determine the effectiveness of preventive training programs in reducing the incidence of ACL injuries, identifying the most effective components and variables that influence their success. Methodology. A documentary, retrospective, and descriptive study based on a narrative review of scientific literature in specialized databases. We included 23 articles (randomized controlled trials) selected by methodological quality criteria according to the PEDro scale. Results. Preventive programs that combine neuromuscular, plyometric, strength, balance, proprioception, and motor control exercises have been effective in reducing ACL injuries, especially among young women and school athletes. Effectiveness was associated with adequate adherence, a minimum frequency of 2-3 times per week, and a duration of at least 6 weeks. Programs focused on the hip musculature improved biomechanical patterns associated with injury risk. Conclusion. The systematic implementation of ACL prevention programs is an effective and cost-effective strategy to reduce the incidence of ACL injuries, improve sports performance, and lower health care costs.